Breaking Barriers: Integrating Padlet to Introduce Environmental Education to Pre-Service Teachers - Rabbianty, Eva Nikmatul; Virdyna, Nina Khayatul; Mulyadi; Azizah, Siti; Roda’i, Mohammad; Abdi Shidqi, Zainal (PANYONARA: Journal of English Education, 2025)
This study explores the integration of Padlet, a web-based digital platform, into environmental education for pre-service teachers at Tadris Bahasa Inggris (TBI) of IAIN Madura, Indonesia, using a mixed-methods approach. A purposive sample of 98 pre-service teachers from 47 Teaching Practice 1 pre-service teachers and 51 TEYL pre-service teachers from TBI participated. The research aims to bridge the gap between environmental education theory and teaching practice by utilizing Padlet as a learning medium. Data collection included pre- and post-surveys on pre-service teachers' perceptions and knowledge of environmental education and technology, along with interviews, observations, and course material analysis. Quantitative data were analyzed using descriptive statistics, while qualitative data underwent thematic analysis. Findings indicate that Padlet significantly enhances student engagement, collaborative learning, and understanding of environmental concepts. The platform's versatility allows for interactive activities that cater to diverse learning styles, fostering critical thinking and environmental consciousness. Despite challenges such as resource constraints and varying levels of digital literacy, the study highlights the potential of digital tools like Padlet to enrich environmental education. The research contributes to the scholarship on innovative pedagogical approaches in sustainability education and offers recommendations for integrating technology into teacher training programs. Findings provide insights into how Padlet supports critical thinking, collaboration, and environmental awareness in teacher education, demonstrating its value as a transformative tool for preparing environmentally conscious future educators.